The time keeper - Albom, Mitch (London : Sphere, 2013)
Banished for centuries, as punishment for trying to measure time, the inventor of the world's first clock is finally granted his freedom, along with a mission: a chance to redeem himself by teaching two people the true meaning of time. He returns to our world and embarks on a journey with two unlikely partners: a teenage girl who is about to give up on life and a wealthy, ageing businessman who wants to live forever. To save himself, he must save them both. Gripping, and filled with deep human truth, this unforgettable story will inspire readers everywhere to reconsider their own notions of time and just how precious it truly is
Keywords: Time -- Fiction; Time -- Management; Fantasy fiction